JEJUNAL DIVERTICULITIS: AN UNUSUAL PRESENTATION OF ACUTE ABDOMEN - Alves, Ana Sofia (2022)
Jejunal diverticula are rare and often incidentally discovered. The most common complication is jejunal diverticulitis, which is frequently overlooked and not routinely considered as a differential diagnosis of acute abdomen because of the location of the diverticula, the patient’s age and the rarity of the disease. Computed tomography (CT) is the imaging modality of choice for diagnosis and evaluation of its extent and complications. We present a 64-year-old woman with a history of progressive abdominal pain, constipation and fever, where jejunal diverticulitis was diagnosed based on CT findings. The CT scan displayed a large, thickened wall, inflammatory mass containing gas and feces-like material adjacent to a jejunal loop, with surrounding inflammatory reactive changes, as well as a few smaller noninflamed diverticula at different levels of the small bowel. The patient was hence diagnosed with uncomplicated jejunal diverticulitis and managed conservatively with complete recovery. The purpose of this article is to illustrate a case of jejunal diverticulitis, as well as to review the current literature regarding the epidemiology, pathogenesis, clinical features, radiologic findings and management of this condition.